Antioxidantes utilizados em óleos, gorduras e alimentos gordurosos - Ramalho, Valéria Cristina [UNESP]; Jorge, Neuza [UNESP] (My University, 2006)
Lipid oxidation is certainly one of the most important alterations that affect both oils or fats and foods that contain them. It is responsible for the development of unpleasant taste and smell in foods, making them unsuitable for consuming. The use of antioxidants permits a longer useful life of these products. This work presents a bibliographic review of research carried out in order to evaluate the antioxidant activity of natural or synthetic substances used in the conservation of food lipid. Among such substances, the following antioxidants are highlighted: butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT), tertiary butylhydroquinone (TBHQ), propyl gallate (PG), tocopherols, phenolic acids and isolated compounds from rosemary and oregano.
Antioxidants used in oils, fats and fatty foods
Keywords: Lipid oxidation; Natural antioxidants; Synthetic antioxidants